2003
DOI: 10.1080/0141861031000109609
|View full text |Cite
|
Sign up to set email alerts
|

A new ferromagnetic thiospinel CuCrZrS4with re-entrant spin-glass behaviour

Abstract: A new thiospinel CuCrZrS 4 has been successfully synthesized by a solid-state chemical reaction. This CuCrZrS 4 exhibits ferromagnetic properties below the Curie temperature at T c = 60 ± 2 K. The appearance of irreversibility between field-cooled (F.C.) and zero-field cooled (Z.F.C.) magnetization is prominent below around 5 K in less than 150 Oe. The ac susceptibility χ AC shows a rapid decrease below ≈10 K. This low-magnetic field behaviour indicates the existence of a reentrant spin glass phase below ≈10 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
5
17
0
Order By: Relevance
“…The effective magnetic moment eff obtained from C is 3.48 B , which is close to the value of 3.87 B expected for the free Cr 3+ ion. As was pointed out by Iijima et al, 21 a large irreversibility between FC and ZFC is observed in the low-temperature range as shown in Fig. 1͑b͒.…”
Section: Methodssupporting
confidence: 55%
See 3 more Smart Citations
“…The effective magnetic moment eff obtained from C is 3.48 B , which is close to the value of 3.87 B expected for the free Cr 3+ ion. As was pointed out by Iijima et al, 21 a large irreversibility between FC and ZFC is observed in the low-temperature range as shown in Fig. 1͑b͒.…”
Section: Methodssupporting
confidence: 55%
“…21 High-purity fine powders of Cu ͑99.99%͒, Cr ͑99.99%͒, Zr ͑99.9%͒, and S ͑99.999%͒ were mixed in stoichiometric ratio and were reacted in a quartz tube at 1023 K for seven days. A powder specimen was reground, pressed into a rectangular bar with an aspect ratio of 1:5, and sintered at 1023 K for two days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Spinel CuCr 2 S 4 is a well known metallic and ferromagnetic compound with the Curie temperature T C of about 400 K. [8][9][10][11] Recently, spinel CuCrZrS 4 was obtained by substituting half of Cr by Zr. [12] It has the same normal spinel structure with Cu in the A site, which is tetrahedrally coordinated with S, and Cr and Zr in the B site, which is octahedrally coordinated. By this substitution, T C is decreased to about 60 K. In addition, a successive magnetic transition suggesting reentrant spin glass was observed at the temperature T G ≈ 10 K. As for the electrical properties, semiconducting behavior of the resistivity was observed.…”
mentioning
confidence: 99%